ANALISIS PENGARUH WORK FAMILY CONFLICT DAN FAMILY WORK CONFLICT TERHADAP INTENTION TO QUIT DENGAN BURNOUT SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan PT. Telekomunikasi Indonesia, Tbk. Wilayah Semarang) - Wulansari, Hesti; Yuniawan, Ahyar (Diponegoro Journal of Management, 2017)
Intention to quit is one of the most widely researched areas in organizational analysis because the lack of competent employees can negatively impact the organization's competitive advantage. Employees who are less competent can be caused by work family conflict and family work conflict when they work. Imbalances of both roles can cause employees experiencing burnout due to prolonged stress. Continuous burnout conditions can trigger employees to have intention to quit from their work. The aim of this study is to describe and analyze the influence of work family conflict and family work conflict on intention to quit with burnout as an intervening variable.This research was conducted by distributing questionnaires to all female employees of PT Telekomunikasi  Indonesia,  Tbk.  Wilayah Semarang  which  amounted  to  46  employees.  Data analysis method used is multiple linear regression analysis. Mechanical testing data used this study include the path analysis and sobel test to test the effect of mediation.The results showed that work family conflict positive and significant influence to burnout and intention to quit, family work conflict positive and significant influence to burnout and intention to quit, and burnout positive and significant influence on intention to quit. Additionally, burnout capable  mediating the  relationship  between  work family conflict  and family work  conflict  on intention to quit.